GE_GERICHTE C/7258/2010 vom 12. März 2013 - GE Cour de justice (2013)
BAIL À LOYER; LOCAL PROFESSIONNEL; ANNULABILITÉ; RÉSILIATION; PRINCIPE DE LA BONNE FOI; IMMISSION; BRUIT; DISPROPORTION | CO.271.1; CO.271.2; CO.271a.1.E; CO.272b.1